Membangun Hukum untuk Kesejahteraan - Atmadjaja, Djoko Imbawani (Jurnal Konstitusi, 2011)
The ideal of Indonesian people to establish the Republic of Indonesia is to build a prosperous and just social and state life. In order to reach such an ideal, any action in contradiction to morality and humanity, except through right and just regulations, is not allowed.